Eksistensi Budaya Dayak dalam Novel Batas Karya Akmal Nasery Basral - Dian Nathalia Inda (Madah: Jurnal Bahasa dan Sastra, 2019)
This research aims to reveal the Dayak culture types which contained in the novel Batas and describe the existence of the culture with the conditions of modern society. This research uses a literary anthropological approach that encompasses tradition, customs, myths, and cultural events in past events. The literature study method is used to collect data. Source of data comes from Batas, while data is analyzed by descriptive analysis method.  The result of the analysis shows that Dayak culture in the novel Batas is a human life tool in the form of mandau and chopsticks; a livelihood in the form of farming and hunting; knowledge system in the form of shifting cultivation systems and preserving forests; social system in the form of custom fines and decapitaing; religious system in the form of spiritual animals, beliefs and Dayak devices; the language and literary system in the form of mantra.; and Dayak ethnic arts in the form of sound art and traditional musical instruments. Dayak culture has been eroded, but there is also a shift in value and meaning because it is no longer relevant to the condition of society today.